27.0k views
1 vote
X2-6x+3 can be written in the form of (x+m)2 +n find the value of m and n

2 Answers

3 votes

Answer:

m = - 3, n = - 6

Explanation:

Expand and compare coefficients of like terms, that is

(x + m)² + n

= x² + 2mx + m² + n

Compare to x² - 6x + 3

comparing coefficients of x- term

2m = - 6 ( divide both sides by 2 )

m = - 3

Comparing constant terms

m² + n = 3 , that is

(- 3)² + n = 3

9 + n = 3 ( subtract 9 from both sides )

n = - 6

User Erickreutz
by
4.6k points
5 votes

Answer:

2(x-3x) + 3

value of X and M is x and -3x respectively

Explanation:

you can factor out the 2 from the 2x -6x and gets the 2(x-3x) while n is the constant that remains the value of 3

I hope this helps

User Disco
by
5.0k points